THE IMPLICATIONS OF THE ENTREPRENEURSHIP EDUCATION COMPONENTS TOWARDS ENTREPRENEURIAL INTENTIONS AMONG NON-ECONOMICS AND BUSINESS STUDENTS IN JAKARTA - Sugeng Riyadi; Atika; Sugeng Ahmad Riyadi (Fakultas Ekonomi Universitas IBA, 2026)
Although not much exposed to commercial and business problems, it does not mean that non-economics and business students have absolutely no interest in entrepreneurship. This study tries to investigate whether entrepreneurship learning in tertiary institutions has a sufficient impact on the entrepreneurial intentions of these non-economic and business students. For this purpose, investigations were made on how the impact of the three components of entrepreneurship education consisting of curriculum, pedagogy, and co-curriculum towards the entrepreneurial intentions of students. Using descriptive and inferential statistical methods through Pearson correlation and multiple regression models, 256 samples were analyzed and interpreted. There were some findings that the entrepreneurial intentions of non-business students were strongly influenced by the components of the curriculum, pedagogy, and curriculum of entrepreneurship education. The better the components, the higher the student's entrepreneurship interest. These findings will help entrepreneurship educators in non-business economics majors, on how they can attract students' entrepreneurial intentions by paying attention to the components of entrepreneurship education explored in this study.